Ireland : 2009 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2009)
Following years as a star performer, Ireland is undergoing a painful adjustment as critical internal imbalances unwind. This 2009 Article IV Consultation highlights that the banking system of Ireland is under considerable stress as asset quality has deteriorated and the global financial crisis has tightened access to wholesale funding. Executive Directors have welcomed the actions taken to safeguard financial stability, backed by ready access to European Central Bank financing. Directors have also supported the authorities' efforts to restructure the financial sector, including the decision to establish the National Asset Management Agency.